2020
DOI: 10.2337/db19-0728
|View full text |Cite
|
Sign up to set email alerts
|

Insulin-Deficient Diabetic Condition Upregulates the Insulin-Secreting Capacity of Human Induced Pluripotent Stem Cell–Derived Pancreatic Endocrine Progenitor Cells After Implantation in Mice

Abstract: The host environment is a crucial factor for considering the transplant of stem cell–derived immature pancreatic cells in patients with type 1 diabetes. Here, we investigated the effect of insulin (INS)-deficient diabetes on the fate of immature pancreatic endocrine cell grafts and the underlying mechanisms. Human induced pluripotent stem cell–derived pancreatic endocrine progenitor cells (EPCs), which contained a high proportion of chromogranin A+ NK6 homeobox 1+ cells and very few INS+ cells, were used. When… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
21
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 22 publications
(21 citation statements)
references
References 32 publications
0
21
0
Order By: Relevance
“…hPSC‐derived pancreatic organoids (hPOs) are more complex than hHOs or hBOs because of the plethora of cells that arise during pancreas differentiation. hPO‐derived pancreatic progenitor cells in a monolayer were incorporated into organoids by day 18 and passaged for long‐term organoid culture every 10–14 days (Hohwieler et al ., 2017; Mochida et al ., 2020). These hPOs and patient‐specific cystic fibrosis‐derived hPOs were orthotopically transplanted into mice and evaluated after 5 weeks.…”
Section: Imaging Organoids and In Vivo Transplantationmentioning
confidence: 99%
“…hPSC‐derived pancreatic organoids (hPOs) are more complex than hHOs or hBOs because of the plethora of cells that arise during pancreas differentiation. hPO‐derived pancreatic progenitor cells in a monolayer were incorporated into organoids by day 18 and passaged for long‐term organoid culture every 10–14 days (Hohwieler et al ., 2017; Mochida et al ., 2020). These hPOs and patient‐specific cystic fibrosis‐derived hPOs were orthotopically transplanted into mice and evaluated after 5 weeks.…”
Section: Imaging Organoids and In Vivo Transplantationmentioning
confidence: 99%
“…Previous publications reported that small molecule induction could imitate the environment during pancreatic endocrine development 10,16,43,[51][52][53][54][55][56] . Generally, an in vitro pancreatic differentiation from SCs could be categorized into 6 differentiation stages: pluripotent/multipotent SCs, mesendoderm, definitive endoderm, pancreatic endoderm, pancreatic endocrine, and pancreatic beta-cells/IPCs 15,57 .…”
Section: Discussionmentioning
confidence: 99%
“…Sex hormones may also influence in vivo maturation of pancreatic progenitors since following implant, glucose-stimulated insulin secretion was observed in female mice before males (234). The systemic environment also provides periodic signals, which might entrain the circadian clock of the implanted stem cell-derived islet cells, leading to their functional maturation (235)(236)(237)(238).…”
Section: Modeling Diabetes With Implanted Stem Cell Derived Islet Cellsmentioning
confidence: 99%